Worker exposure to ultrafine particles during carbon black treatment - Urszula Mikołajczyk; Stella Bujak-Pietrek; Irena Szadkowska-Stańczyk (Nofer Institute of Occupational Medicine, 2015)
Background: The aim of the project was to assess the exposure of workers to ultrafine particles released during handling and packing of carbon black. The assessment included the results of the measurements performed in a carbon black handling plant before, during, and after work shift. Material and Methods: The number concentration of particles within the dimension range 10-1000 nm and 10-100 nm was assayed by a condensation particle counter (CPC). The mass concentration of particles was determined by a DustTrak II DRX aerosol concentration monitor. The surface area concentration of the particles potentially deposited in the alveolar (A) and tracheo-bronchial (TB) regions was estimated by an AeroTrak 9000 nanoparticle monitor. Results: An average mass concentration of particles during the process was 6-fold higher than that before its start, while a 3-fold increase in the average number concentration of particles within the dimension range 10-1000 nm and 10-100 nm was observed during the process. At the same time a 4-fold increase was found in the surface area concentration of the particles potentially deposited in the A and TB regions. Conclusions: During the process of carbon black handling and packing a significantly higher values of each of the analysed parameters, characterizing the exposure to ultrafine particles, were noted. Med Pr 2015;66(3):317-326